Microstructure evolution and mechanical properties of TiAl/GH536 joints vacuum brazed with Ti–Zr–Cu–Ni filler metal. (March 2022) - Jiang, Chen-yang; Li, Xiao-qiang; Wan, Bao; Zhu, De-zhi; Qu, Sheng-guan; Yang, Chao
Abstract: In this study, a novel Ti–Zr–Cu–Ni amorphous filler metal was fabricated and applied to vacuum brazing of TiAl alloy and Ni-based superalloy (GH536). The effects of brazing temperature on the interfacial microstructure and mechanical properties of the joints were analyzed. Three different regions, the isothermal solidification layer Ⅰ, continuous reaction layer Ⅱ and continuous diffusion layer Ⅲ, were formed in the joints after brazing. The SEM and EDS results show that brazing temperature plays an important role in element diffusion, microstructure evolution and metallurgical quality of brazed joints, while the thickness of layer Ⅱ and Ⅲ was basically not affected by brazing temperature. The obtained joints showed excellent shear strength both at room temperature and elevated temperature. With the increase of brazing temperature, the shear strength of joints at room temperature firstly increased and then decreased. The optimal shear strength of 279 MPa was obtained after brazing at 1100 °C for 10 min. With the increase of test temperature, the shear strength of joints obtained at 1110 °C/10 min firstly decreased, then increased, and decreased again, with the maximum value of 156 MPa at 600 °C. The shear fracture mainly occurred in the thinnest layer Ⅱ and the fracture morphology exhibited typical cleavage fracture characteristics. Highlights: A novel Ti–Zr–Cu–Ni amorphous filler metal was fabricated to vacuum braze TiAl alloy and Ni-based superalloy (GH536). The joints brazed at 1110 °C for 10 min obtain the maximum shear strength of 279 MPa at room temperature. The cracks mainly originate between AlNi2Ti and Al3NiTi2 phases owing to their non-coherent relationship, and propagate along Al3NiTi2.